Diagnostic use of CA 125 values measured on the 2nd and 14th days of the menstrual cycle in endometriosis - Avşar, Hüseyin Aytuğ; Kurt, Sefa; Celiloğlu, Murat; Timur, Tunç (Journal of Surgery and Medicine, 2022)
Background/Aim: This study examines the difference of serum CRP and CA 125 levels between the menstrual and non-menstrual phases of the menstrual cycle (days 2 and 14) and aims to investigate the diagnostic value of these markers for the early diagnosis of endometriosis. Methods: There were 36 patients in the study group and 30 patients in the control group (n = 66) in this prospective case-control study. The patients in the study group, who were prediagnosed with endometriosis, were tested for serum CA 125 and CRP on the 2nd and 14th days of menstrual cycle preoperatively (during menstruation and non-menstrual phase) and underwent surgery. The women in the control group were patients who visited the outpatient clinic for a regular checkup without any gynecological complaints. Results: The CA 125 levels were significantly higher on the 2nd day of the menstrual cycle than the 14th day in the study group [108.15 (90.33) U/mL and 58.60 (39.53) U/mL, respectively, P < 0.001]. In the control group, the CA 125 levels were also significantly higher on the 2nd day than the 14th day [22.97 (15.42) U/mL and 13.82 (6.82) U/mL, respectively, P < 0.001]. When the comparison was made between the CRP levels on the 2nd and 14th day for the study group [4.52 (4.45) mg/L and 2.82 (3.79) mg/L, respectively], the levels were significantly higher on the 2nd day (P < 0.001). The difference of CA 125 and CRP levels between the days [for the study group: ΔCA 125 = 49.55 (56.89) U/mL, ΔCRP = 1.69 (3.45) mg/L and for the control group ΔCA 125 = 9.14 (11.95) U/mL, ΔCRP = 1.42 (4.74) mg/L] were higher for both markers in the study group, and the differences with the control group were statistically significant (P < 0.001 for ΔCA 125 and P = 0.033 for ΔCRP). Conclusion: Our data indicates that it may be possible to support the diagnosis with the evaluation of CA 125 levels during different phases of menstruation separately.